2022
DOI: 10.1055/a-1932-6937
|View full text |Cite
|
Sign up to set email alerts
|

Basic Concepts and Activation Modes in Visible-Light-Photocatalyzed Organic Synthesis

Abstract: Visible-light photocatalysis has established itself as a promising sustainable and powerful strategy to access reactive intermediates, i.e. radicals and radical ions, under mild reaction conditions using visible light irradiation. This field enables the development of formerly challenging or even previously inaccessible organic transformations. In this tutorial review, an overview of the essential concepts and techniques of visible light-mediated chemical processes and the most common types of photochemical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…Similarly, the initial independent reports of synthetic e-PRC in 2020 by Wickens et al (using NpMI ) and Lambert et al (using DCA ) have also attracted considerable comment (note that DCA has been used as a photocatalyst for several proposed conPET reactions, as well as e-PRC) . In their original report, Lambert et al pointed to a published excited state lifetime for *DCA ·– of 13.5 ns, which was expected to be long enough to allow for diffusive encounters with substrate molecules and subsequent SET (though highly concentration-dependent, it has been suggested as a rule of thumb that this usually requires lifetimes >1 ns) . Unfortunately, reinspection of the prior literature revealed that this value, which was based on fluorescence quenching of in situ electrochemically generated solutions of DCA ·– , had subsequently been found to be erroneous .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the initial independent reports of synthetic e-PRC in 2020 by Wickens et al (using NpMI ) and Lambert et al (using DCA ) have also attracted considerable comment (note that DCA has been used as a photocatalyst for several proposed conPET reactions, as well as e-PRC) . In their original report, Lambert et al pointed to a published excited state lifetime for *DCA ·– of 13.5 ns, which was expected to be long enough to allow for diffusive encounters with substrate molecules and subsequent SET (though highly concentration-dependent, it has been suggested as a rule of thumb that this usually requires lifetimes >1 ns) . Unfortunately, reinspection of the prior literature revealed that this value, which was based on fluorescence quenching of in situ electrochemically generated solutions of DCA ·– , had subsequently been found to be erroneous .…”
Section: Resultsmentioning
confidence: 99%
“…The first methods developed to perform the direct ortho-arylation of anilines rely on radical coupling reactions through photochemical 14 as well as thermal processes. The former will be discussed in the following section.…”
Section: Direct C(sp 2 )-H Ortho-arylation Of Anilinesmentioning
confidence: 99%
“…The Sanford group first evaluated dual catalytic crosscoupling reactions in 2011 and 2012 by performing the ortho-selective arylation of a range of arenes, bearing different directing groups, with aryl diazonium 63a or diaryliodonium 63b salts at room temperature using a palladium-based catalyst in combination with a ruthenium-or iridiumbased photocatalyst under visible-light irradiation. 14 Among the substrates, N-(ortho-tolyl)acetamide could be efficiently arylated at the ortho position with both PhN 2 BF 4 and Ph 2 IOTf in 89% and 69% GC yields, respectively (Scheme 27, eqs. 1 and 2).…”
Section: Dual Catalytic Cross-coupling Reactionsmentioning
confidence: 99%
“…The most common photoactivation modes involved in organic synthesis are photoinduced electron transfer (PET) and photoinduced energy transfer (EnT) which were covered in a separate basic introductory review on photocatalysis. 10 However, some other advanced activation modes of organic molecules exist that are covered in this section and these do not always involve a photocatalyst: photoinduced hydrogen-atom transfer (HAT) (Section 2.1), proton-coupled electron transfer (PCET) (Section 2.2), electron donor-acceptor (EDA) photoactivation (Section 2.3), and excited-state transition-metal (*TM) catalysis (Section 2.4).…”
Section: Advanced Photoactivation Modesmentioning
confidence: 99%
“…The basics of photocatalysis are covered in a complementary introductory review. 10 This review first describes advanced activation modes in organic photocatalysis, with particular attention on the explanation of the reaction mechanisms (Section 2). Subsequently, a selection of emerging techniques in photocataly-sis such as dual catalysis, excited radical ion chemistry, triplet-triplet annihilation upconversion, and near-infrared (NIR)/deep red light photocatalysis are discussed in Section 3.…”
Section: Review Synthesismentioning
confidence: 99%